eVOLVER - construção e automação de plataforma de cultura celular e utilização de métodos alternativos para a medição de pH - Freitas, Augusto Vieira D’Assunção (Universidade Federal de São Carlos, 2023)
The work is limited to going deeper into the construction stages of an eVOLVER, within the scope of its open source nature. ´Areas such as software, hardware and others components will be explored and explained in as much detail as possible, taking taking into account the author's areas of activity. It will still undergo a bibliographic review. analysis of academic articles in search of alternative methods for measuring pH, discussing and detailing promising studies to, in the end, choose the one that most adapt to eVOLVER, in order to forward future efforts of the next ones involved with the project. The author also points out that the process was the result of teamwork, recognizing and thanking the collaboration of other EBI members - Eduarda Nicoletto, Marisa Brito and Matheus Chitan, and also the advisor Jos´e Guilherme Ribas Franco, in the reconstruction of the system. The author also thanks Regis Terenzi Neuenschwander, Patricia Henriques Nallin and Dr. Nadia Maria Vieira Sampaio for her contributions and project orientation.
eVOLVER - construction and automation of a cell culture platform and use of alternative methods for pH measurement
Keywords: EVOLVER; CIENCIAS EXATAS E DA TERRA::FISICA